Youth Depression Alleviation‐Augmentation with an anti‐inflammatory agent (YoDA‐A): protocol and rationale for a placebo‐controlled randomized trial of rosuvastatin and aspirin. Issue 1 (5th November 2015) - Quinn, Amelia L.; Dean, Olivia M.; Davey, Christopher G.; Kerr, Melissa; Harrigan, Susy M.; Cotton, Sue M.; Chanen, Andrew M.; Dodd, Seetal; Ratheesh, Aswin; Amminger, G. Paul; Phelan, Mark; Williams, Amber; et al.
Abstract: Aim: There is growing support for the role of inflammation and oxidative stress in the pathophysiology of major depressive disorder (MDD). This has led to the development of novel strategies targeting inflammation in the treatment of depression. Rosuvastatin and aspirin have well‐documented, anti‐inflammatory and antioxidant properties. The aim of the Youth Depression Alleviation: Augmentation with an anti‐inflammatory agent (YoDA‐A) study is to determine whether individuals receiving adjunctive anti‐inflammatory agents, aspirin and rosuvastatin experience a reduction in the severity of MDD compared with individuals receiving placebo. Methods: YoDA‐A is a 12‐week triple‐blind, randomized controlled trial funded by the National Health and Medical Research Council, Australia. Participants aged 15–25, with moderate‐to‐severe MDD, are allocated to receive either 10 mg/day rosuvastatin, 100 mg/day aspirin, or placebo, in addition to treatment as usual. Participants are assessed at baseline and at weeks 4, 8, 12 and 26. The primary outcome is change in the Montgomery–Åsberg Depression Rating Scale (MADRS) from baseline to week 12. Results: The study is planned to be completed in 2017. At date of publication, 85 participants have been recruited. Conclusion: Timely and targeted intervention for youth MDD is crucial. Given the paucity of new agents to treat youth MDD, adjunctive trials are not only pragmatic and 'real‐world', but additionally aim to target shortfalls in conventional medications. This study has the potential to first provide two new adjunctive treatment options for youth MDD; aspirin and rosuvastatin. Second, this study will serve as proof of principle of the role of inflammation in MDD.